Dynamic FDG PET/CT on bladder paraganglioma: A case report - Taninokuchi Tomassoni, Makoto; Cattabriga, Arrigo; Gaudiano, Caterina; Ciccarese, Federica; Corcioni, Beniamino; Bianchi, Lorenzo; Schiavina, Riccardo; Brunocilla, Eugenio; Golfieri, Rita (Frontiers in Medicine, 2022)
Paraganglioma is characterized by equivocal clinical manifestations and arriving to a suspicion might be challenging. Nevertheless, diagnostic imaging and nuclear medicine are a fundamental part of the diagnosis and management of this particular neuroendocrine tumor (NET). We herein report a rare case of bladder paraganglioma with unusual onset and specific PET/CT characteristics that led to its recognition.